STAT3 suppresses the AMPKα/ULK1‐dependent induction of autophagy in glioblastoma cells. Issue 14 (6th June 2022) - Bhattacharya, Sujoy; Yin, Jinggang; Yang, Chuanhe; Wang, Yinan; Sims, Michelle; Pfeffer, Lawrence M.; Chaum, Edward
Abstract: Despite advances in molecular characterization, glioblastoma (GBM) remains the most common and lethal brain tumour with high mortality rates in both paediatric and adult patients. The signal transducer and activator of transcription 3 (STAT3) is an important oncogenic driver of GBM. Although STAT3 reportedly plays a role in autophagy of some cells, its role in cancer cell autophagy remains unclear. In this study, we found Serine‐727 and Tyrosine‐705 phosphorylation of STAT3 was constitutive in GBM cell lines. Tyrosine phosphorylation of STAT3 in GBM cells suppresses autophagy, whereas knockout (KO) of STAT3 increases ULK1 gene expression, increases TSC2‐AMPKα‐ULK1 signalling, and increases lysosomal Cathepsin D processing, leading to the stimulation of autophagy. Rescue of STAT3‐KO cells by the enforced expression of wild‐type (WT) STAT3 reverses these pathways and inhibits autophagy. Conversely, expression of Y705F‐ and S727A‐STAT3 phosphorylation deficient mutants in STAT3‐KO cells did not suppress autophagy. Inhibition of ULK1 activity (by treatment with MRT68921) or its expression (by siRNA knockdown) in STAT3‐KO cells inhibits autophagy and sensitizes cells to apoptosis. Taken together, our findings suggest that serine and tyrosine phosphorylation of STAT3 play critical roles in STAT3‐dependent autophagy in GBM, and thus are potential targets to treat GBM.